Development of Newly Formulated Emulsion Containing PhytoSpherix™ and Actigym™ Marine Ingredient for Skin Protection Potentia (Asian Journal of Pharmaceutics (AJP), 2025)
PhytoSpherix™ is a nanoparticle derived from non-genetically modified sweet corn, isolated fromthe plant, and Actigym™ is a marine ingredient created by a Bermudan bacterium (a Bacillus sp.). Therefore,our objectives were to (i) formulate an emulsion containing PhytoSpherix™ and Actigym™ marine ingredients,(ii) stabilize the emulsion with Sustoleo™ MCT and SustOleo™ GMS, (iii) determine the sun protection factor(SPF), (iv) analyze ultraviolet A/ultraviolet B (UVA/UVB) protection, and (v) assess in vivo skin melanin,erythema, elasticity, and moisture content. Materials and Methods: A new oil-in-water emulsion was prepared,incorporating PhytoSpherix™ and Actigym™ marine ingredient, using a mixture of cetyl alcohol, hydrogenatedrapeseed oil, triheptanoin, glyceryl stearate, and distilled water. Various tests were conducted, including acceleratedthermal stability, pH measurement, color, smell, phase separation, liquefaction, rheology, SPF, UVA/UVBprotection, irritation, and in vivo effects on skin (melanin, erythema, elasticity, hydration, image visualization, andsensory evaluations). Results: The emulsion demonstrated excellent stability in both short and long-term testing,maintained a pH of 5.81, showed no phase separation, and had a viscosity of 1.042 Pa.s with a pseudoplastic trend,indicating shear-thinning behavior. It exhibited satisfactory safety profiles, causing no irritation in rats or humanvolunteers. In vitro testing revealed a SPF value of 23.70 and a UVA/UVB ratio of 0.51, providing effective UVBprotection. Furthermore, it improved skin elasticity and moisture retention while reducing melanin and erythemacompared to the control. Conclusion: The newly formulated emulsion was deemed stable and showed promisingeffects against UV radiation on the skin, warranting further investigation.